Avaliação da resistência ao cisalhamento por extrusão, push-out, de pinos de fibra de vidro cimentados à dentina radicular de dente bovinos com diferentes cimentos resinosos - estudo "in vitro" - Daleprane, Bruno (2010)
Due to the need for knowledge of the strength of the union of the agents of the resin cements used to-retain the intracanal post, this in-vitro study aimed to evaluate the union of different resin cements to the root canal walls, from the adhesive cementation of fiber glass post, verifying the union by the resistance to the “push-out” test in different regions of the canal. For this study, we used roots of 36 bovine teeth divided into three groups, which were cemented Fiberglass Reforpost no 3 pins. Group A: Panavia F / ED Primer, Group B: RelyX ARC/ Scotchbond Multi-Purpose Plus and Group C: RelyX Unicem. After cementation, specimens were prepared for mechanical testing of “push-out” in different radicular thirds. For statistical analysis, we used the Kruskal Wallis method and for comparing means and to identify groups that differ in each third the Mann Whitney test was used. It was found that for all groups, the cervical third bond strength was similar, whereas for the middle third of the group B and C were statistically similar and both higher than in Group A, and the apical the Group B was superior to both Group A and the lower values of Group C. When comparing this force within each group, it observed that Group C had a uniform bond strength at different depths of root, since the Group A has the best value in the cervical third, and the middle thirds apical and similar to group B and the third cervical was superior to both apical and similar to a medium (p≤0,05). We conclude with a study that the type of cement used influenced the bond strength. Those cementation systems requiring treatment prior to cementation dentin, there was influence the depth of the canal, giving rise to reduced strength of adhesion to approaching the most the apical region, unlike that of cement adhesive presented value for uniform adhesion.